UHL 2412 English for Academic Communication Module - Asiah, Kassim; Fathiah Izzati, Mohammad Fadzillah; Hafizoah, Kassim; Hamizah, Zahari; Mohd Shafiq, Abdul Jabar; Nur Syafawati, Sabuan; Suriya Kumar, Sinnadurai (Centre for Modern Languages and Human Sciences, 2017)
UNIT 1: LISTENING SKILLS Types of Listening; Listening Strategies